INNOVATION FOR THE DEVELOPMENT OF PRIMARY SCHOOL IN SCIENCE, MATHEMATICS, AND TECHNOLOGY - Ratchatawimon, Somkhuan; Thongphubate, Thanong; Chotientip, Tassanee (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2024)
This research aimed to (1) analyze the development of primary schools in science, mathematics, and technology according to the IPST standards in schools with 1-120 students, and (2) create an innovation for school development based on the IPST standards. A mixed-method research approach was employed, with a sample of 374 schools selected through simple random sampling for the quantitative part, and 12 key informants chosen through purposive sampling for the qualitative part, including participation in a Professional Learning Community (PLC) process. The key informants included (1) five school administrators from the Quality School Project in Science, Mathematics, and Technology according to IPST standards, (2) five experts from IPST, and (3) two educational supervisors. Research instruments included questionnaires, PLC process recording forms, and innovation evaluation forms. The data were analyzed using frequency, mean, and standard deviation for the quantitative data, and content analysis for the qualitative data. The research results revealed that (1) the current development of primary schools was at the highest level in all aspects, and (2) regarding the innovation for primary school development, the "Six-G Innovation" was developed, consisting of 6 components and 27 indicators: 1) Policy and Planning (G1), 2) Support (G2), 3) Teacher Development (G3), 4) Learning Management (G4), 5) Supervision (G5), and 6) Participation (G6). This innovation effectively promoted the development of primary schools in science, mathematics, and technology through the PDCA quality cycle.